2020
DOI: 10.1029/2019gl086550
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Indirect Effects on Cirrus Clouds Based on Global Aircraft Observations

Abstract: Cirrus clouds have large climate impacts, yet aerosol indirect effects on cirrus microphysical properties remain highly uncertain. There is a lack of observational analysis on thermodynamic, dynamical, and aerosol indirect effects simultaneously, which limits the quantification of each effect. Using seven National Science Foundation aircraft campaigns, impacts of temperature, relative humidity, vertical velocity, and aerosols are individually quantified. Nonmonotonic correlations of ice water content, ice crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…with μ T and ν T as in equation (17). Here, q j and g  are respectively the mixing ratio of the moist air and the acceleration due to gravity of the Earth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…with μ T and ν T as in equation (17). Here, q j and g  are respectively the mixing ratio of the moist air and the acceleration due to gravity of the Earth.…”
Section: Discussionmentioning
confidence: 99%
“…The transposition operation is represented by the superscript T and μ T as in equation (17). The frictional force f vis…”
Section: Conservation Of Momentum Of Moist Airmentioning
confidence: 99%
See 1 more Smart Citation
“…Chylek et al (2006) showed an increase in ice crystal size during the more polluted winter months compared with cleaner summer months over the eastern Indian Ocean. Using a global-scale dataset of multiple flight campaigns, Patnaude and Diao (2020) isolated individual effects on cirrus clouds from temperature, RHi, vertical velocity (w) and aerosol number concentrations (Na). They found that when Na is 3 -10 times higher than average conditions, it shows strong positive correlations with cirrus microphysical properties such as IWC, Ni and number-weighted mean diameter (Di).…”
mentioning
confidence: 99%